Sistem Penghitung Jumlah Pengguna pada Ruang Kerja menggunakan Background Subtraction - Nico Kurniawan; Lily Puspa Dewi; Henry Novianus Palit (Jurnal Infra, 2020)
The computer center at Petra Christian University has not been able to measure the utilization of laptop space, so it cannot know the number of users who are using laptop space facilities. Despite the existence of a registration system in using these facilities, the number of student registration lists with the number of users who use the laptop room is not appropriate because there are students who do not register first. For this reason, the system for calculating the number of users uses background subtraction using the MOG2 and GMG methods so that it can help find out the number of people who use laptop room facilities.In this study will create a program to count the number of users by detecting people, and create a website program system to display data on the number of users. This system was created using C ++, and a website was created using PHP and MySQL databasesThe results of this study indicate that the lighting factor and frame resolution are very influential on the accuracy of the user's detection. The effect of detection lighting can be seen from the results of the confusion matrix which shows that what is detected mostly exceeds the number of users in the room. While the effect of resolution on detection can be seen from the results of F1 scores on one of the lighting videos that showed using a resolution of 1280x720 the results of the MOG2 method reached 68% and the GMG method reached 40%. After reducing the frame to 640x360, the average value of MOG2 reaches 86% and the GMG method reaches 67%.